2013
DOI: 10.1097/cco.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Current status of interleukin-10 and regulatory T-cells in cancer

Abstract: Purpose of review Tumor growth elicits antigen-specific cytotoxic as well as immune suppressive responses. Interleukin-10 (IL-10) is a key immune-suppressive cytokine produced by regulatory T-cells (Tregs) and by helper T-cells (TH). Here we review pleiotropic functions of IL-10 that impact the immune pathology of cancer. Recent findings The role of IL-10 in cancer has become less certain with knowledge of its immune stimulatory functions. IL-10 is needed for T-helper cell functions, T-cell immune surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
187
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(192 citation statements)
references
References 184 publications
4
187
0
1
Order By: Relevance
“…Using an exogenous IL-10 administration strategy and various mouse models of CRC we have consistently shown over the last years that IL-10 is suppressing carcinogenesis (9,36,38). The results of the present study add value to the key role of IL-10 in protecting mucosal surfaces from cancer (40).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Using an exogenous IL-10 administration strategy and various mouse models of CRC we have consistently shown over the last years that IL-10 is suppressing carcinogenesis (9,36,38). The results of the present study add value to the key role of IL-10 in protecting mucosal surfaces from cancer (40).…”
Section: Discussionsupporting
confidence: 68%
“…The role of Treg in cancer is paradoxical (6,40,41). Treg have been traditionally viewed as cancerpromoting cells based on their function to suppress protective antineoplastic immune responses (40,41). However, our original studies in mice showing that the adoptive transfer of Treg not only protected but it further counteracted already established intestinal, breast and prostate neoplasia (6,9,10,25,36,42,43), are now supported by many other animal and human studies (8,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 IL10 is an immunosuppressive cytokine secreted by T cells and has been shown to be stimulated by PD-L1. 41,42 This change in cytokine secretions indicated effective PD-L1 knockdown and enhanced cytotoxic T-cell function. It has been demonstrated that CD8 + T cell inflaming GCs contain high PD-L1 expression, suggesting that adaptive immune resistance is active in GC.…”
mentioning
confidence: 95%
“…3 In the context of inflammation-driven intestinal dysplasia, IL-10-production by T-regulatory cells is essential in the control of tumorigenesis. 4 Similarly, recombinant IL-10 can ameliorate disease symptoms in murine models of inflammatory bowel disease (IBD). 5 However, the results of clinical trials in IBD patients have been disappointing due to dose-limiting systemic toxicity.…”
mentioning
confidence: 99%